2000
DOI: 10.1039/b001013h
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent reversible polymers formed from cyclic sugar- and aromatic boronic acid-based bolaamphiphiles

Abstract: Glucuronamide-based bolaamphiphiles are found to form a reversible, linear polymolecular array, via a boronate ester linkage attached to the 1,2-positions of the pyranose or furanose ring, upon complexation with an aromatic boronic acid-based homologue in aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 15 publications
(22 reference statements)
0
39
0
1
Order By: Relevance
“…Reversible reactions are presently receiving increasing attention and provide a means for developing new materials exhibiting unusual features. Recent covalent polymers investigated for their reversible properties have included entities based on various reactions, such as transesterification (12)(13)(14)(15), transetherification (16), Diels-Alder reaction (17,18), [2 ϩ 2] photodimerization (19), radical reaction (20), and boronate ester formation (21).…”
Section: Reversibility Exchange and Diversitymentioning
confidence: 99%
“…Reversible reactions are presently receiving increasing attention and provide a means for developing new materials exhibiting unusual features. Recent covalent polymers investigated for their reversible properties have included entities based on various reactions, such as transesterification (12)(13)(14)(15), transetherification (16), Diels-Alder reaction (17,18), [2 ϩ 2] photodimerization (19), radical reaction (20), and boronate ester formation (21).…”
Section: Reversibility Exchange and Diversitymentioning
confidence: 99%
“…[8] The polycondensation of diboronic acids with sugar derivatives as linkers has been investigated by the groups of Shinkai [11] and Shimizu. [12] Again it was found that the polymerization is a reversible process, which depends on the conditions. An alternative way to generate dynamic polymers with boron centers in the backbone is the polymerization by dative B-N bonds.…”
Section: Introductionmentioning
confidence: 98%
“…58 Of particular note is that the reversible polymer formation and dissociation were achieved depending on pH conditions of the aqueous solutions used.…”
Section: Ph-dependent Reversible Polymer Formation From Bola-form Dermentioning
confidence: 99%
“…[56][57][58] The self-assembling behavior and the obtained morphologies were examined using confocal laser scanning, dark-field, polarized, and phase-contrast light microscopy. When saturated, hot aqueous solutions containing 1(n) or 3(n) were allowed to gradually cool and stand at room temperature, a variety of supramolecular fibers (nanofibers) with nanometer-sized dimension spontaneously and reproducibly appeared, strongly dependent on both the spacer length and the even/odd spacer carbon numbers ( Figure 2).…”
Section: Formation Of Self-assembled Supramolecular Fibersmentioning
confidence: 99%